Characterization of the local knowledge of the tree component in cattle farms - Coral, Diana Lucia; Coral, Jhon Pablo; Muñoz G, Diego Andrés (Revista de Ciencias Agrícolas, 2011)
The study was carried out in the municipality of Pupiales, south of Narino Department. At 0°54' north latitude and 77°39' west, at 3,014 m.a.s.l, with average temperature of 12°C, The local knowledge on the woody component and their interaction with the livestock, pasture, soil and biodiversity, was studied, identifying the traditional knowledge at ten villages of the municipality, in three different strata: stratum I, cattle properties of 0.1 to 3 hectares; stratum II, cattle of 3.1 a 6 and stratum III, cattle over to 6.1 hectares. The methodology was used; the AKT5 program (Agroecological Knowledge Toolkit) was used for the compilation and representation of the agroforestry knowledge. And an adaptation of the method of formalization proposed by Bentley et al., (2001). The data were analyzed through descriptive statistic. 35 themes of local knowledge were recognized, coming from 30 key informants (10 for stratum) validated by means of 45 randomized farmers. The descriptive analyses recognize 14 representative topics in the area, outstanding the local tendency for the medicinal use of the woody species, further more to get is recognized and an ecological valuation of the alive fences, as unit preponderant landscape of the area. The statistical analyses suggest divergences in the creation, formalization, legitimation of the knowledge among farmers, places and strata. The validation process proved to be valid and representative of the knowledge base created in AKT5.